Searching for less perturbed elliptical orbits around Europa - Dos Santos, J. Cardoso [UNESP]; Carvalho, J. P.S.; Prado, A. F.B.A.; De Moraes, R. Vilhena (IOP Publishing, 2015)
Space missions intending to visit Europa, one of the famous Galilean's moons of Jupiter, are among the most important topics in space activities today. There is an increasing interest in the scientific community to send spacecrafts to be inserted into Europa's orbit, with goals like mapping its surface and gravitational field. From the quality of the observations until the orbital maneuvers, the required aspects for the success of the mission will depend on the orbits used by the spacecraft. The present work searches for less perturbed elliptical orbits around Europa, because they are very important, since these orbits are expected to be more stable to place the spacecraft. The development of the study is based on the net effects of the perturbing forces over the time, evaluated by the integral of those forces with respect to the time. The value of this integral depends both on the dynamical model and the orbit of the spacecraft. Jupiter's third-body perturbation and the J2 and J3 terms of the gravitational potential of Europa are the perturbing forces considered. The results presented here are obtained by performing numerical integrations of the perturbing forces, and they show the locations of the less perturbed orbits.